2004
DOI: 10.1002/cncr.20364
|View full text |Cite
|
Sign up to set email alerts
|

Anal cancer incidence and survival: The Surveillance, Epidemiology, and End Results experience, 1973–2000

Abstract: BACKGROUNDAnal cancer is a rare malignancy of the anogenital tract that historically has affected women at a greater rate than men.METHODSThe authors analyzed changing trends in incidence rates and 5‐year relative survival percentages for patients with anal cancer. The publicly available data used in the current study were obtained from the Surveillance, Epidemiology, and End Results (SEER) Program, a system of population‐based tumor registries in the United States.RESULTSThe incidence of anal cancer was simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

17
374
1
28

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 573 publications
(420 citation statements)
references
References 26 publications
17
374
1
28
Order By: Relevance
“…This is in line with reports from the USA of increases in incidence in periods between 1940 and 2003 3,4,[16][17][18][19] and from other European countries. [20][21][22] As in the 2 most recent European studies, we observed that the increase was particularly evident in women.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This is in line with reports from the USA of increases in incidence in periods between 1940 and 2003 3,4,[16][17][18][19] and from other European countries. [20][21][22] As in the 2 most recent European studies, we observed that the increase was particularly evident in women.…”
Section: Discussionsupporting
confidence: 92%
“…5,30 The 5% annual increase in the incidence of AIN2/3 in the period 1998-2008 is even higher than the overall increase in anal cancer. This corresponds to the findings of Johnson et al, 4 who observed increased incidences of anal carcinoma in situ in both genders between 1973 and 2000 in the USA, but with a higher rate in men. This may reflect, first, that the likelihood of being screened and having the disease diagnosed at an early stage has increased, and, second, that men at risk are more likely to be screened than women.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The incidence of anal cancer is increasing due to its risk factors [11] , such as anal-genital human papillomavirus (HPV) infection, immunosuppression associated with human immunodeficiency virus or transplantation and smoking [12,13] . In the present patient, there was no symptom of anal-genital HPV infection or immunosuppression.…”
Section: Discussionmentioning
confidence: 99%